Analisis Hubungan Antara Pajak Daerah dengan Pendapatan Asli Daerah Kota Malang Tahun 2018 - 2023 - Firda Aulia Azzahro; Nia Firnanda; Riska Yulia Devi; Aufa Azizatunnisa; Novi Khoiriawati (Journal Economic Excellence Ibnu Sina, 2025)
The research in this journal is to see the contribution of local taxes in Regional Original Revenue (PAD) and the growth of local taxes from 2018 to 2023 in Malang City. The methodology applied in this research is a quantitative descriptive approach. Data was obtained from the official website of Malang City Bapenda. The results of this analysis reveal that the contribution of local taxes to local revenue in the period 2018 to 2023 is quite significant, reaching 76.63%. The largest source of local tax contribution comes from the Acquisition Tax on Land and Building (BPHTB) which accounts for around 37.1% of the total local tax, while the average growth of local tax and local revenue between 2018 and 2023 is at 7.1% of the total population.